More everything forever : AI overlords, space empires, and Silicon Valley's crusade to control the fate of humanity - Becker, Adam, 1984- (Basic Books, 2025)
"Tech billionaires have decided that they should determine our futures for us. According to Elon Musk, Jeff Bezos, Sam Altman, and more, the only good future for humanity is one powered by technology: trillions of humans living in space, functionally immortal, served by superintelligent AIs. In More Everything Forever, science writer Adam Becker investigates these wildly implausible and often profoundly immoral visions of tomorrow-and shows why, in reality, there is no good evidence that they will, or should, come to pass. Nevertheless, these obsessions fuel fears that overwhelm reason-for example, that a rogue AI will exterminate humanity-at the expense of essential work on solving crucial problems like climate change. What's more, these futuristic visions cloak a hunger for power under dreams of space colonies and digital immortality. The giants of Silicon Valley claim that their ideas are based on science, but the reality is darker: they come from a jumbled mix of shallow futurism and racist pseudoscience. More Everything Forever exposes the powerful and sinister ideas that dominate Silicon Valley, challenging us to see how foolish, and dangerous, these visions of the future are"--